Direct Medical Cost Inpatient ACS-STEMI at Sardjito Hospital 2017-2018 - M. Fiqri Zulpadly; Anif Nur Artanti; Dian Eka Ermawati; Sholichah Rohmani; Heru Sasongko; Wisnu Kundarto (Universitas Sebelas Maret, 2022)
Cardiovascular disease is the main cause of human death worldwide. This disease is also a major burden in health financing, due to direct costs of treatment and hospitalization. One type of cardiovascular disease is Acute Coronary Syndrome (ACS). The incidence of ACS in Indonesia is still the highest with a prevalence rate of 7.2% and continues to increase every year. This study aimed to determine the average direct medical costs of new ACS-STEMI patients who are hospitalized at Dr. Sardjito Hospital Yogyakarta period 2017-2018 and the factors that influence the cost of the treatment statistically. This research was an observational study with a descriptive retrospective research design using data from medical records and the finance (accounting) department. The sampling technique used in this study was purposive sampling based on patients who met the inclusion criteria. A total of 495 patients matched the inclusion criteria and the average of the components of direct medical costs incurred by inpatients was IDR48,926,665 with an average length of stay of 5 days. Statistical test results showed that the categories of gender, age, and payment method were not significantly associated with the average total cost of care for ACS-STEMI patients (p>0.05). Meanwhile, the categories of length of stay and treatment regimen were significantly correlated to the average total cost of care for ACS-STEMI patients (p<0.05). The average total cost of new ACS-STEMI patients undergoing inpatient treatment amounted to IDR48,926,665 which was significantly influenced by the category of the length of hospitalization and therapeutic regimen.